Monsoon Asia: a reader on South and Southeast Asia - Henley, David; Wickramasinghe, Nira (Critical, connected histories, 2023)
Monsoon Asia was the first venue of global trade, a zone of encounters, exchanges, and cultural diffusion. This book demonstrates the continuing fertility of the Monsoon Asia perspective as an aid to understanding what South/Southeast Asia, as a connected space, has been in the past and is today. Sixteen tightly knit chapters, written by experts from perspectives ranging from Indology and philology to postcolonial and transnational studies, offer a captivating view of the region, with its rich and variegated history shaped by commonalities in human ecology, cultural forms, and religious practices. The contributions draw upon extensive research and a thorough command of the most recent scholarship. This volume will be an invaluable text for anyone interested in South and Southeast Asia, and for more specialized students in the fields of global and Indian Ocean history, transcultural studies, archaeology, linguistics, and politics.